Volatility Spillover on IDX Energy Sector - Ardhiani Fadila; Siwi Nugraheni; Dienni Ruhjatini Sholihah (Program Studi Akuntansi FPEB UPI, 2022)
This study aimed to determine the spillover volatility factors from the stock returns on IDX Energy Sector firms. It focused on 3 types of factors, including 1) economy, especially crude oil prices, 2) market, such as inflation, exchange rate, and real GDP growth, and 3) firm specific-factors, such as ROE, Firm Size, and DER. A total of 39 out of 66 firms were chosen for analysis while data was collected from 2011 to 2020. Furthermore, the Panel Data analysis method was used to examine the main aspects of stock return spillover volatility. The results showed that crude oil prices, inflation, exchange rates, and real GDP growth significantly partially affected stock returns in the Energy Sector, while ROE, Firm Size, and DER had no effect.